Análisis de efectos por la interconexión de generación distribuida en el sistema de protección de sobrecorriente de la red de distribución troncal (Alimentador) 13.8 Kv vía Buena Fe - Gorozabel Bizueta, Jefferson Agustín (2019)
The current research focuses in the determination of the effects that could generate the interconnection of distributed generation in the electrical protection system of overcurrent of a radial distribution gird through simulations that measures or emulate the real behavior of the different electrical magnitudes in the grid. The confiability of determining the effects that the distributed generation in the electrical protections can cause, is used as case of study the troncal distribution gird (feeder) 13,8kV Vía Buena Fe and its main overcurrent protection system. As a result of the simulations, it was found that the introduction of DG in the feeder generated a series of effects that make it difficult the correct operation of overcurrent protection electrical system, which vary in relation of the location of the fault, the location of the unit of DG and the number of units of DG present in the feeder. It is necessary to highlight that the effects generated in the protection devices based on the maximum generation of the DG unit used, and these may vary in relation to the power of generation of the unit. Keywords: Distributed generation, overcurrent protection system, distribution system